2020
DOI: 10.1007/s13197-020-04417-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and antioxidant profiling of Ocimum sanctum

Abstract: The leaves of Ocimum sanctum were extracted in methanol (OsM) and sequentially fractionated with n-hexane (OsH), ethylacetate (OsE) and butanol (OsB) to find the best extraction solvent for antioxidants from the herb known for its medicinal values. OsB was rich in both total polyphenolic content (TPC) (212.26 ± 6.3 mg GAE/ g extract) and total flavonoid contents (TFC) (54.51 ± 3.5 mg QE/g extract). OsE also had significantly high TPC (202.71 ± 5.5 mg GAE/g extract). The EC 50 based on DPPH (3.91 ± 0.3 lg/ml), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 32 publications
(59 reference statements)
5
47
1
2
Order By: Relevance
“…The mass fragmentation was performed with varying collision energy 4V/ 100 DA with an offset of 6V. .326-Rosmarinic acid and 595.518-Apigenin 6,8-di-glucoside The mass fragmentation patterns of these compounds are found to be in agreement with that of previous reports [9,15]. Alkaloids such as Piperine (m/z 286.1576) and piperanine (m/z 288.1687) has been reported previously from Piper nigrum [16,17] and are known for their immunomodulatory properties [18,19].…”
Section: Optimization Of Lc/ms Methodssupporting
confidence: 86%
“…The mass fragmentation was performed with varying collision energy 4V/ 100 DA with an offset of 6V. .326-Rosmarinic acid and 595.518-Apigenin 6,8-di-glucoside The mass fragmentation patterns of these compounds are found to be in agreement with that of previous reports [9,15]. Alkaloids such as Piperine (m/z 286.1576) and piperanine (m/z 288.1687) has been reported previously from Piper nigrum [16,17] and are known for their immunomodulatory properties [18,19].…”
Section: Optimization Of Lc/ms Methodssupporting
confidence: 86%
“…Fewer studies were observed with other solvents such as hot water extract that showed similar results to hydromethanolic and hydroethanolic extractions in the same plant [106]. On the other hand, some studies further fractionated the extract to isolate the compounds, as seen in the infusion of O. campechianum [107] and the methanolic extract of O. gratissimum and O. sanctum [100,101].…”
Section: Extraction Methods Of Flavones From Lamiaceae Plants 41 Conventional Methodsmentioning
confidence: 99%
“…Polar solvents such as methanol, ethanol, and aqueous mixtures have been used to obtain extracts from species including O. basilicum, O. gratissimum, O. sanctum, and O. tenuiflorum with good results [84,[99][100][101][102][103][104]. Less used, but also effective in the extraction of flavones, are solvents such as diethyl ether, which is useful to extract such flavones as nevadensin and salvigenin in O. basilicum [105].…”
Section: Extraction Methods Of Flavones From Lamiaceae Plants 41 Conventional Methodsmentioning
confidence: 99%
“…The herbs Giloy, Tulsi and Kalmegh are renowned for their various health benefits in Ayurveda. [ 18 19 20 ] These herbs have exhibited antiviral,[ 26 27 28 ] anti-inflammatory,[ 29 30 31 ] immunomodulatory,[ 32 33 34 ] antiallergic,[ 35 36 37 ] antipyretic,[ 38 39 40 ] and antioxidant[ 41 42 43 ] potential in scientific studies. Chyawanprash is a traditionally renowned ayurvedic health supplement that has been studied extensively in scientific and clinical studies for its immunostimulatory,[ 44 45 ] antioxidant and anti-inflammatory potentials.…”
Section: Discussionmentioning
confidence: 99%